A study of diurnal variation in peak expiratory flow rates in healthy adult female subjects in South India - Jenny Jayapal (Wolters Kluwer Medknow Publications, 2014)
Background: Peak Expiratory Flow Rate (PEFR) reflects the strength and condition of respiratory muscles and the degree of airflow limitation in large airways. PEFR shows hour to hour variation that follows a specific pattern in asthmatics and healthy individuals. Adequate data is not available for the diurnal variation in normal individuals who are students in professional courses and had a sedentary life style. Hence, this study was undertaken to study the diurnal variation in peak expiratory flow rates in healthy adult female subjects in South India. Materials and Methods: Peak expiratory flow rate was recorded in 50 adult healthy female students aged 18-23 years and studying in professional courses. Mini Wright's peak flow meter was used to measure the peak expiratory flow rate. PEFR were recorded at 7-8 a.m., 10-11 a.m., 1-2 p.m., 4-5 p.m., and 7-8 p.m. for two consecutive days. Results: On analysis of PEFR records of individual subjects, it was seen that there was an overall dip in the morning at 7-8 h PEFR, which increased in the daytime, peaking in the afternoon at 1-2 p.m. and eventually decreased in the night. Subjects did not show the peak PEFR values at the same time point, 10% of subjects had a rise in PEFR in the early morning, afternoon (1-2 p.m.) peak was observed in 48% subjects and evening (4-5 p.m.) peak was observed in 16% subjects. 14% subjects showed a peak in the night time (7-8 p.m.) PEFR values. Conclusion: This study provided the preliminary reference data of diurnal variation of peak expiratory flow rate in healthy adults. Since, there is a variation in the peak expiratory flow rate recorded during different time points of the day; hence, to compare the PEFR between individuals it is advisable to record the PEFR at the same time point.